Beyond The Reason-Revelation Dichotomy: Reconstructing Al-Ghazali’s Epistemology of Religion - Imam Wahyuddin; Agus Himawan Utomo; Arqom Kuswanjono; M. Mukhtasar Syamsuddin (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This article examines Al-Ghazali’s epistemology of religion with particular attention to the relationship between reason and revelation. Contrary to the common portrayal of Al-Ghazali as an opponent of philosophy, it argues that he develops an epistemological framework that transcends the classical dichotomy between rationalism and theological authority. Employing a historical-conceptual reconstruction of key texts, including Iḥyāʾ ʿUlūm al-Dīn, Tahāfut al-Falāsifah, Al-Qisṭās al-Mustaqīm, Al-Munqidh min al-Ḍalāl, and Qānūn al-Taʾwīl, the study demonstrates that Al-Ghazali does not merely reconcile reason and revelation but assigns each a distinct epistemic function. Reason serves not only as an interpretive instrument but also as a means of verifying prophetic legitimacy, thereby establishing the epistemic authority of revelation. On this basis, the article argues that Al-Ghazali’s thought offers a dialogical and integrative model of religious knowledge in which rational inquiry and revelation operate within a single epistemic framework. This finding contributes not only to Ghazalian studies but also to contemporary philosophy of religion by proposing an alternative to both rationalist and fideistic approaches to religious justification